Utilization of Microcontroller Based Sensors in the Implementation of Independent Learning at MA YPKP Sentani Jayapura: Pemanfaatan Sensor Berbasis Mikrokontroler Dalam Implementasi Merdeka Belajar di MA YPKP Sentani Jayapura - Hardi Hamzah; Tiyas Nur Janah; Jepron Ben Wenda; Meson Yekwa; Rachmadani O. Susilowati; Muhammad N. Agriawan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Schools are required to implement the independent learning curriculum. This curriculum provides an open space for children to explore and express their interest in learning so that in the future children will have a good spirit of competence and good characteristics. The application of technology in schools is very suitable for the context of independent learning. One of the problems experienced by schools is that they have not utilized technology such as microcontrollers in the teaching and learning process. This community service program is implemented through 3 stages, namely the preparation, implementation, and evaluation stages. In the preparation stage, observations and interviews were carried out. At the program implementation stage, the teaching and learning process is carried out using a project-based learning model. The evaluation stage is carried out during the service activity process and afterwards. During the process, students are evaluated. Based on the results of the implementation of activities, it is known at MA YPKP Sentani that the implementation of the independent learning program using a project-based learning model that utilizes microcontroller-based sensors has gone well. It is hoped that the results of this activity can become a benchmark for the development of the learning process as targeted by the activity objectives.